2015
DOI: 10.1007/s00330-015-3983-x
|View full text |Cite
|
Sign up to set email alerts
|

CT pre-operative planning of a new semi-implantable bone conduction hearing device

Abstract: • Preoperative temporal bone CT is essential for determining Bonebridge device suitability. • Mastoid under-pneumatisation and prior mastoidectomy predict a retrosigmoid Bonebridge position. • 3D simulation software is recommended for precise device positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 13 publications
0
10
0
4
Order By: Relevance
“…Thus, AP may be used as a parameter for preoperative evaluation, to remind the surgeon of the possibility of dural or sigmoid sinus exposure during preparation of the bone bed for BC-FMT. Eric K, et al found the use of Lifts, or sigmoid sinus or dural depression, necessary to accommodate the BC-FMT in the majority of cases, including most mastoid placements [33].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, AP may be used as a parameter for preoperative evaluation, to remind the surgeon of the possibility of dural or sigmoid sinus exposure during preparation of the bone bed for BC-FMT. Eric K, et al found the use of Lifts, or sigmoid sinus or dural depression, necessary to accommodate the BC-FMT in the majority of cases, including most mastoid placements [33].…”
Section: Discussionmentioning
confidence: 99%
“…20 A pre-operative temporal bone computed tomography (CT) scan using three-dimensional software is used to accurately assess the most suitable position for the bone conduction floating mass transducer, which is localised to two positions: the retrosigmoid region or the sinodural angle (presigmoid region) according to different factors such as mastoid hypoplasia, previous mastoid surgery and sigmoid sinus exposure. 21 Many studies have reported positively on the efficacy, safety and acoustic benefit of the device in conductive hearing loss, mixed hearing loss and single-sided deafness. 22,23 Vogt et al suggested that the sound localisation abilities of children with congenital unilateral conductive hearing loss improved when acoustic stimuli were presented to the impaired (Bonebridge implanted) side.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, detailed preoperative, CT-based surgical planning was recommended in those situations [ 2 , 6 , 7 , 12 , 13 , 15 , 17 , 20 , 22 , 27 30 , 34 ]. The introduction of BCI Lifts increased the probability that the BC-FMT could be fitted to the bone with 4‑mm lifts in up to 100% of patients older than 9 years [ 20 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperatively, the temporal bone is evaluated to determine placement of the BC-FMT. Several methods and tools have been described for this task, varying from a detailed visual analysis and two-dimensional (2D) measurements of standard computed tomography (CT) scans to sophisticated planning tools and preoperative "virtual surgery" [2,6,7,12,13,15,17,[27][28][29][30]34].…”
Section: Surgical Techniquementioning
confidence: 99%